Data Mining : a Tutorial-Based Primer, Second Edition. - Roiger, Richard J. (Chapman & Hall/CRC data mining and knowledge discovery series., 2017)
"Provides a comprehensive introduction to data mining with a focus on model building and testing, as well as on interpreting and validating results. The text guides students to understand how data mining can be employed to solve real problems and recognize whether a data mining solution is a feasible alternative for a specific problem. Fundamental data mining strategies, techniques, and evaluation methods are presented and implemented with the help of two well known software tools."--